The Impact of CRM on Business or MSME Performance: A Literature Review - Budi Utami; Sudarmiatin Sudarmiatin (Journal of Social Science, 2022)
This study aims to determine the effect of Customer Relationship Management (CRM) on Business Performance or SMEs. The research method uses a systematic literature review, the scientific article database is taken from Scopus Q1, Q2 and Q3 on Publish or Perish. The screening is carried out specifically for scientific articles. Using the keywords CRM and company performance (MSMEs), as well as scientific articles with a minimum number of citations Customer Relationship Management (CRM) has a positive relationship to company performance (MSMEs) both in terms of financial performance and non-financial performance.